Facile and robust construction of a 3D-hierarchical NaNbO3-nanorod/ZnIn2S4 heterojunction towards ultra-high photocatalytic H2 production. Issue 7 (7th March 2022) - Zhang, Juhua; Gu, Huajun; Wang, Xinglin; Zhang, Huihui; Li, Lingfeng; Wang, Xiaohao; Dai, Wei-Lin
Abstract : The robust 3D-hierarchical NaNbO3 -nanorod/ZnIn2 S4 heterojunction shows a striking H2 -evolution rate of 30.04 mmol h −1 g −1 under sunlight, the highest among reported NaNbO3 and ZnIn2 S4 -based photocatalysts to date. Abstract : It is imperative but still challenging to develop heterojunction photocatalysts for efficient interfacial charge carrier separation in photocatalytic hydrogen evolution (PHE) reactions. Encouragingly, in this work, we constructed a 3D hierarchical NaNbO3 /ZnIn2 S4 heterojunction for the first time by in situ coating thin-layered ZnIn2 S4 nanosheets on the external surface of NaNbO3 nanorods via a facile solvothermal method. A striking hydrogen evolution rate of 30.04 mmol h −1 g −1 was attained using NaNbO3 /ZnIn2 S4 as a photocatalyst under simulated sunlight irradiation, which is almost 110-fold and 11-fold higher than that of bare NaNbO3 and ZnIn2 S4, respectively, and is the highest value obtained thus far among reported NaNbO3 and ZnIn2 S4 -based catalysts. This extraordinary improvement in the photocatalytic performance is mainly due to two reasons. Firstly, the difference in conduction band position and the intimate contact between NaNbO3 and ZnIn2 S4 facilitate interfacial charge separation from NaNbO3 to ZnIn2 S4 . Secondly, the unique hierarchical heterostructure not only affords a more diffused surface area but also serves as a 3D supporting platform to generate more fruitful proton reduction sites, realizing a maximized photocatalytic activity. Additionally, density functional theory (DFT) calculations on the heterojunction further revealed the electron density distribution at the heterointerface and a close-to-neutral Gibbs free energy of hydrogen adsorption (Δ G H ). Hence, the present work can provide fresh guidance for the synthesis and development of more NaNbO3 and ZnIn2 S4 -based composite photocatalysts for related applications in photocatalysis.